Evaluasi Penggunaan Antibiotik pada Pasien Tifoid Rawat Inap di Rumah Sakit Ulin Banjarmasin dengan Metode Gyssens dan ATC/DDD - Antung Sinta Dewi; Saftia Aryzki; Kunti Nastiti (SENTRI: Jurnal Riset Ilmiah, 2025)
Typhoid is a gastrointestinal infection caused by Salmonella typhi. The disease is transmitted through contaminated food and beverages and can spread from infected individuals. Symptoms typically appear 1–3 weeks after exposure and include high fever, malaise, headache, constipation, diarrhea, and enlargement of the liver and spleen. At a hospital in South Kalimantan in 2022, 80% on cases of typhoid treatment can use antibiotics. One study showed resistance of salmonella typhi to antibiotics such as ampicillin, amoxicillin, and chloramphenicol. To evaluate the use of antibiotics both quantitatively using the ATC/DDD methods and qualitatively using the Gyssens methods for hospitalized typhoid patients at Ulin Regional Hospital, Banjarmasin, in 2024. This study uses quantitative data with the Gyssens method and qualitative data with the ATC/DDD method in typhoid patients. The research was conducted over one month, from June to July 2025, at Ulin Hospital Banjarmasin the Sample 7. Quantitative evaluation showed a total of 488,93 DDD/100 patient-days with DU 90% analysis. Qualitative evaluation using the Gyssens method indicated that 71.42% of antibiotic use was rational. Ampicillin was categorized as IVa (1 patient), a combination of Metronidazole, Ceftazidime, and Cefixime was categorized as IVa (1 patient), and five patients receiving combination therapy fell under category 0 (rational). The majority of antibiotic use was considered rational. Antibiotic use in hospitalized typhoid patients at Ulin General Hospital Banjarmasin in 2024 was largely rational.